Problem of philosophical research of political and legal culture as part of Chernivtsi myth - Zhmundulak, Dmytro (Skhid, 2013)
The article deals with the cultural and historical retrospection moments of the formation of political and legal culture of the city Chernivtsi as a dynamic component of the "myth of Chernivtsi". The problem is interpreted in the light of local and global aspects of multiculturalism, as a rich and complex history of this city is characterized by ethnic and cultural diversity of, and, simultaneously, stable desire for peaceful coexistence among different ethnic communities in the context of the changing types of socio-political culture.